The Influence of Organizational Culture and Work Motivation on Employee Performance Through Organizational Citizenship Behavior of Sahid Montana Hotel Employees in Malang City - Gilang Rasmardi Astry; Mokh. Natsir; Tanto Gatot Sumarsono (Asian Journal of Applied Business and Management, 2023)
The purpose of this study is to analyze the effect of organizational culture and work motivation on OCB and the performance of Sahid Montana hotel employees and to analyze the influence of organizational culture and work motivation on employee performance if mediated by OCB. The data analysis technique used is path analysis. The results of the study show that the better the organizational culture and the higher the employee's work motivation, the better organizational citizenship behavior will be. The better the organizational culture and the higher the employee motivation, the better employee performance will be. Organizational culture and work motivation affect employee performance through OCB. To be able to improve the performance of Sahid Montana hotel employees, leaders need to create a good organizational culture by keeping abreast of science and technology developments and paying attention to employees to achieve satisfaction. Employees are motivated by opportunities to innovate, and leaders can provide suggestions and constructive criticism.